2005
DOI: 10.1167/iovs.04-1427
|View full text |Cite
|
Sign up to set email alerts
|

Cone-like Morphological, Molecular, and Electrophysiological Features of the Photoreceptors of theNrlKnockout Mouse

Abstract: Many morphological, molecular, and electrophysiological features of the Nrl(-/-) photoreceptors are cone-like, and strongly distinguish these cells from rods. This retina provides a model for the investigation of cone function and cone-specific genetic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
229
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(253 citation statements)
references
References 65 publications
24
229
0
Order By: Relevance
“…Although the dorsal/ventral M/S-cone gradient is preserved in Nrl −/− mice, more S-opsin sensitivity is seen in Nrl −/− cones than in wild-type cones from comparable dorsal/ventral levels of the retina (Nikonov et al, 2006). Consistent with the above electrophysiological measures, the ultrastructural analysis showed that the Nrl −/− retina has much shorter cone-like outer segments with disrupted morphology and cone-like nuclei with decondensed chromatin Daniele et al, 2005). Whorls and rosettes are seen at early ages and thinning of the outer nuclear layer occurs later on , similar to retinal histopathology in rd7 mice.…”
Section: Animal Studiessupporting
confidence: 66%
“…Although the dorsal/ventral M/S-cone gradient is preserved in Nrl −/− mice, more S-opsin sensitivity is seen in Nrl −/− cones than in wild-type cones from comparable dorsal/ventral levels of the retina (Nikonov et al, 2006). Consistent with the above electrophysiological measures, the ultrastructural analysis showed that the Nrl −/− retina has much shorter cone-like outer segments with disrupted morphology and cone-like nuclei with decondensed chromatin Daniele et al, 2005). Whorls and rosettes are seen at early ages and thinning of the outer nuclear layer occurs later on , similar to retinal histopathology in rd7 mice.…”
Section: Animal Studiessupporting
confidence: 66%
“…[24][25][26][27] In the retina of Nrl knockout mice, Fischer et al 24 show that the histology of rosette structures corresponds with the round or ovoid features with highly reflective annular lines observed in speckle noise-reduced SD-OCT. Although it remains unclear whether the rosettes in animal models are same as the ORT in human patients, 26 this correspondence suggests that the ORT is comprised of rearranged neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of the transcription factor NRL, rod progenitor cells divert to an S-cone-like phenotype. Thus, the nrl 2/2 retina is made up of a small number of 'authentic' S-and M-cones and a large number of S-cone-like cells which do not exhibit precisely native S-cone behavior (7,8). In addition, although it is well established that the cone opsin promoter we used drives COP-T expression in S-and M-cones, it originates from the M-opsin gene and the levels of expression in M-versus S-cones have not been quantified.…”
Section: Discussionmentioning
confidence: 99%